FACTORS AFFECTING THE DEVELOPMENT OF UMKM IN KLAMBIR LIMA KEBUN VILLAGE HAMPARAN PERAK DISTRICT DELI SERDANG - Sebayang, Saimara A M (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to determine the factors that affect the development of UMKM in Klambir Lima Kebun Village, Hamparan Perak District, Deli Serdang Regency. This research is a field research, where quantitative primary data through an instrument in the form of a questionnaire is taken directly from UMKM actors who are the people of Klambir Lima Kebun Village. The sampling technique used is simple random sampling where sampling of members of a population is carried out randomly without regard to the strata present in that population. Asample of 30 respondents was taken. The results of data processing and factor analysis using SPSS version 25 show that the factors that affect the development of UMKM include: the quality of human resources, production systems, financial management systems, marketing strategies and partnership systems. Partially and simultaneously the quality of human resources, production systems, financial management systems, marketing strategies and partnership systems have a positive and significant effect on the development of UMKM with a percentage contribution of 99.6%.